2023
DOI: 10.1002/bse.3414
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the equifinal configurations of prompting green supply chain integration and subsequent performance outcome

Abstract: Although green supply chain integration (GSCI) is essential for enterprises to address environmental challenges, existing literature mainly focuses on the net effect of a single factor that cannot well explain and guide the implementation of GSCI. Based on technology–organization–environment (TOE) framework, we develop a configurational framework and propose that GSCI depends on the interactions between perceived institutional force, green human resource management (GHRM), and big data analytics capability (BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…Second, all highperformance configurations necessitated at least two dimensions of GSCI as core conditions. Therefore, in line with prior studies, we recognized the significance of implementing GSCI for achieving sustainable performance (Feng and Sheng, 2023;Kong et al, 2021;. Moreover, perceived institutional force emerged as a core condition in all configurations that facilitated high sustainable performance.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Second, all highperformance configurations necessitated at least two dimensions of GSCI as core conditions. Therefore, in line with prior studies, we recognized the significance of implementing GSCI for achieving sustainable performance (Feng and Sheng, 2023;Kong et al, 2021;. Moreover, perceived institutional force emerged as a core condition in all configurations that facilitated high sustainable performance.…”
Section: Discussionsupporting
confidence: 82%
“…, 2023). Furthermore, studies have suggested that institutional forces shape firms' capacity to acquire resources and their level of integration within the supply chain, thereby impacting the effectiveness of GSCI on firm performance (Feng and Sheng, 2023; Yang et al. , 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Before formulating the formal questionnaire, we studied the related literature extensively and established an initial English questionnaire based on mature scales. Then, the translation and back-translation methods were used to avoid ambiguity (Feng and Sheng, 2023). Later, a preliminary test was conducted and the initial questionnaire was revised repeatedly according to the test situation to increase the readability.…”
Section: Research Design 31 Sample and Data Collectionmentioning
confidence: 99%